Are Financial Analysts' Earnings Forecasts Rational? - Wu, Chun Hua (2008)
Prior studies provide conflictive findings of rational expectation tests on financial analysts forecasts based on different assumptions of loss function. Most studies using the ordinary least squares (OLS) regression tests which implicitly assume analysts face a quadratic loss function document that financial analysts do not incorporate information rationally when they form their forecasts. In contrast, other recent studies argue that financial analysts actually face a linear loss function and find no economic evidence of analysts forecasts irrationality based on the least absolute deviation (LAD) regression that implicitly assume a linear loss function. This paper re-examines the rational expectation hypothesis on earnings forecast using both loss functions. Consistent with prior studies, the findings suggest that under the OLS regression, analysts forecasts are irrational; however, no evidence of forecast irrationality is found under the LAD regression tests. Thus, prior findings of analysts forecasts inefficiency may be largely driven by a quadratic loss function.